The Pendampingan Balita Resiko Stunting Dalam Upaya Peningkatan Asupan Zat Gizi Makro Dan Status Gizi Pada Program (MSIB) Di Wilayah Kerja Puskesmas Tambak Wedi, Surabaya: Vol 1.No 1 (2024) : JURNAL PENGABDIAN MASYARAKAT MERDEKA MEMBANGUN NEGERI (ABDIMERKA) - Diana, Putri; Rahmdhaniah; Dwi Putri Rahmawati3 (Jurnal Pengabdian Masyarakat Merdeka Membangun Negeri, 2024)
Stunting or short stature can lead to stunted growth, impaired cognitive and motor development, suboptimal body size and impaired metabolism. Stunting also causes a decrease in immunity so that it can lead to diabetes, obesity, etc. The purpose of this service is to increase the intake of macronutrients and the nutritional status of toddlers in the work area of the Tambak Wedi Surabaya Health Center. The mentoring uses interview techniques and direct measurement techniques. Based on this data, it shows that the assistance of toddlers has succeeded in increasing the intake of macronutrients and the nutritional status of toddlers at risk of stunitng in the work area of the Tambak Wedi Health Center in Surabaya. Macronutrient intake plays a role in providing energy and is directly related to the nutritional status of toddlers. The results of the nutrition assistance program not only increase the intake of macronutrients, but also play an important role in improving the nutritional status of toddlers who are at risk of stunting